Meta-Analysis of Caenorhabditis elegans Transcriptomics Implicates Hedgehog-Like Signaling in Host-Microbe Interactions - Zárate-Potes, Alejandra; Ali, Irtiqa; Ribeiro Camacho, Margarida; Brownless, Hayley; Benedetto, Alexandre (Frontiers in Microbiology, 2022)
Controlling nematode-caused diseases that affect cattle and crops world-wide remains a critical economic issue, owing to the lack of effective sustainable interventions. The interdependence of roundworms and their environmental microbes, including their microbiota, offers an opportunity for developing more targeted anthelminthic strategies. However, paucity of information and a currently narrow understanding of nematode-microbe interactions limited to specific infection contexts has precluded us from exploiting it. With the advent of omics approaches to map host-microbe genetic interactions, particularly in the model roundworm Caenorhabditis elegans, large datasets are now available across multiple models, that enable identification of nematode-microbe-specific pathways. In this work we collected 20 transcriptomic datasets documenting gene expression changes of C. elegans exposed to 20 different commensal and pathogenic microbes, performing gene enrichment analyses followed by functional testing using RNA interference directed toward genes of interest, before contrasting results from transcriptomic meta-analyses and phenomics. Differentially expression analyses revealed a broad enrichment in signaling, innate immune response and (lipid) metabolism genes. Amongst signaling gene families, the nematode-divergent and expanded Hedgehog-like signaling (HHLS) pathway featured prominently. Indeed, 24/60 C. elegans Hedgehog-like proteins (HRPs) and 15/27 Patched-related receptors (PTRs) were differentially expressed in at least four microbial contexts, while up to 32/60 HRPs could be differentially expressed in a single context. interestingly, differentially expressed genes followed a microbe-specific pattern, suggestive of an adaptive microbe-specific response. To investigate this further, we knocked-down 96 individual HHLS genes by RNAi, using high-throughput assays to assess their impact on three worm-gut infection models (Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis) and two worm-commensal paradigms (Comamonas sp., and Bacillus subtilis). We notably identified new putative infection response genes whose upregulation was required for normal pathogen resistance (i.e. grl-21 and ptr-18 protective against E. faecalis), as well as commensal-specific host-gene expression changes that are required for normal host stress handling. Importantly, interactions appeared more specific than shared. Our results thus implicate the Hedgehog-like signaling pathway in the modulation and possibly fine-tuning of nematode-microbe interactions and support the idea that interventions targeting this pathway may provide a new avenue for anthelmintic development.